ENRICHMENT OF THE GALACTIC DISK BY THE NEUTRON CAPTURE ELEMENTS (Ba and Eu) - Gorbaneva, T. I. (Одеські астрономічні публікації, 2017)
The abundances of Ba and Eu were determined for 38 red giant stars in the metallicity range -0.6<[Fe/H]<+0.25 using the spectral synthesis technique. The spectra were obtained with spectrograph ELODIE (Haute Provence Observatoire, France), the resolwing power is 42000, S/N is more than 100. For the Ba and Eu lines the effects of hyperfine structure and isotope shifts are included, assuming the isotope ratios of the r-process component of the solar system material. Abundances of the n-capture element (Ba and Eu) for 38 red giants with metallicities [Fe/H] from -0.6 to +0.25 and correlation of the [Ba/Eu] ratios with stellar metallicities are present. The [Ba/Eu] ratio reflects substantial production of Ba in the s-process for the stars with metallicity -0.6<[Fe/H]<+0.25.